Spiral Jetty, geoaesthetics, and art: Writing the Anthropocene. (April 2019) - Ballard, Susan; Linden, Liz
Despite the call for artists and writers to respond to the global situation of the Anthropocene, the 'people disciplines' have been little published and heard in the major journals of global environmental change. This essay approaches the Anthropocene from a new perspective: that of art. We take as our case study the work of American land artist Robert Smithson who, as a writer and sculptor, declared himself a 'geological agent' in 1972. We suggest that Smithson's land art sculpture Spiral Jetty could be the first marker of the Anthropocene in art, and that, in addition, his creative writing models narrative modes necessary for articulating human relationships with environmental transformation. Presented in the form of a braided essay that employs the critical devices of metaphor and geoaesthetics, we demonstrate how Spiral Jetty represents the Anthropocenic 'golden spike' for art history, and also explore the role of first-person narrative in writing about art. We suggest that art and its accompanying creative modes of writing should be taken seriously as major commentators, indicators, and active participants in the crafting of future understandings of the Anthropocene.